ATTENDANCE OF SEMINARS IN TRADITIONAL AND BLENDED FORMS OF EDUCATION - I. V. Kharlamenko (Высшее образование в России)
The article analyzes class attendance in different forms of education: traditional and blended ones. Literature review shows that attendance is linked with students' academic performance. The author gained the data on attendance of seminars by the 4th-year students in the biological department ofMSU and applied mathematical methods to process the data. The attendance of seminars by students has been analyzed in two educational forms: traditional learning (face-to-face classroom seminars were accompanied by autonomous paper work) and blended learning (face-to-face classroom seminars were accompanied by autonomous work on a specially created educational wiki website). The results show that blended learning, more than traditional learning contributes to the formation of a high level of attendance.